2006
DOI: 10.1007/s10228-005-0321-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetic analyses of snakeheads (Perciformes: Channidae) using mitochondrial DNA sequences

Abstract: Mitochondrial DNA sequences of approximately 1.5 kbp including the NADH dehydrogenase subunit 2 (ND2) gene and its flanking gene regions were determined for 20 species from the freshwater fish family Channidae and 3 species from Nandidae, Badidae, and Osphronemidae. Channa orientalis and C. gachua had an approximately 170-bp insertion between the tRNA Met and ND2 genes, where a 5′-half of the insertion was similar to the 5′-end portion of the ND2 gene and a 3′-half was homologous to the tRNA Met gene. This ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 28 publications
6
36
1
1
Order By: Relevance
“…Although the prevalence of C. asiatica was 25.0%, this result should be considered with caution because only 4 individuals were necropsied. Channa argus and C. asiatica are very close in terms of their morphologic and phylogenetic relationships, as well as in their feeding preferences (Li et al, 2006). Channa argus and C. asiatica may be infected accidentally by consumption of other fish.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prevalence of C. asiatica was 25.0%, this result should be considered with caution because only 4 individuals were necropsied. Channa argus and C. asiatica are very close in terms of their morphologic and phylogenetic relationships, as well as in their feeding preferences (Li et al, 2006). Channa argus and C. asiatica may be infected accidentally by consumption of other fish.…”
Section: Discussionmentioning
confidence: 99%
“…Snakeheads are highly valued as food and are used in fisheries, aquaculture, and the life-food trade and can be found in most fishmarkets in SEA. Their taxonomy and systematic has been controversial in the past, the first molecular frameworks for channid phylogenetics were published based on mitochondrial genes [177] or combining mitochondrial and nuclear genes [178]. More recently, Serrao and colleagues [179] established a Channidae DNA barcode reference library based on 250 DNA barcodes sequences representing 25 species 5.…”
Section: Border Biosecurity and Invasive Speciesmentioning
confidence: 99%
“…For the present study these species were precisely identified based on the morphomeristic keys described by Jayaram (1999) and Vishwanath et al (2007). Efforts were earlier made to address the problems related to species identification and to assess the genetic variability by employing classical morphological criteria, karyomorphology, and protein and DNA markers (Dhar and Chatterjee 1986;Banerjee et al 1988;Li et al 2006). Except for a few karyological studies (Nayyar 1966a;Manna and Prasad 1973;Rishi and Rishi 1981;Dhar and Chatterjee 1986;Naorem and Bhagirath 2006), these species have not been investigated thoroughly using chromosome banding and DNA markers for deducing the evolutionary and phylogenetic relationships among them.…”
Section: Introductionmentioning
confidence: 99%